Analysis of inflation, population, and economic growth on poverty in Muslim-majority provinces in Indonesia - Melinda Anisya Sari; Mohammad Rofiuddin (Indonesian Journal of Islamic Economics Research, 2022)
This study aims to determine the effect of inflation, population, and economic growth on poverty in Indonesia. The object of this research is the Muslim majority population in 10 provinces in Indonesia in 2017–2021. In this study, the data used are time series obtained from Statistics Indonesia (BPS). The method used to see the effect of using a panel data regression approach is the Random Effect Model. The study results show that simultaneously, inflation has no effect on poverty, population size also has a positive effect on poverty, while economic growth has a negative effect on poverty. Of all the variables, inflation, population, and economic growth simultaneously significantly affect poverty in 10 provinces with the majority Muslim population in Indonesia.